Positive Criminal Law Regulations Regarding the Crime of Cyberbullying as a Form of Cyber Crim - Chandra Adam, Richard (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to examine positive criminal law regulations related to criminal acts of cyberbullying as a form of cybercrime in Indonesia. Through a legislative approach, this research analyzes related legal developments in cyberbullying, with a focus on Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) and amendments through Law Number 19 of 2016. The research results show that the ITE Law provides a strong legal basis for dealing with cyberbullying, with heavy sanctions for perpetrators. However, this regulation has also drawn criticism regarding potential restrictions on freedom of speech. Thoughtful law enforcement, education, and awareness of online ethics are important in addressing this problem. Legal changes and a holistic approach are needed to face challenges in the ever-evolving digital era.